Evaluation of blood omega-3 and omega-6 levels in healthy female dogs and female dogs with mammary tumours - TUZLU, T.; SARIBAY, M.K.; KOLDAS ÜRER, E.; KÖSE, A.M.; GÖZER, A.; YAKAN, A.; ÖZSOY, Ş.Y. (Journal of the Hellenic Veterinary Medical Society, 2021)
The study was designed to determine the blood levels of omega fatty acids, which have an important role in the etiology of mammary tumours, in healthy and female dogs with mammary tumour. The study was carried out in 9 female dogs with histologically confirmed mammary tumour and a control group with 9 healthy female dogs without clinical mammary neoplasia. 10 ml cephalic blood samples were collected by using a 21G x 1.5΄΄ blood collecting needle into anticoagulated tubes before the surgical removing of the mammary masses. Mastectomy was performed in all female dogs with mammary tumours and all the mammary specimens were sent to laboratory for histopathological examination. According to histopathological diagnosis results, all of the tumours were found to be malignant. Omega-3 levels were found to be higher in healthy female dogs (p<0.001) whereas omega-6 levels were higher in female dogs with mammary tumour (p<0.001). These observations support the notion tha thigh levels of omega-3 fatty acids might proove to have a protective role on mammary tumor formation in female dogs, while increased levels of omega-6 fatty acids may be related to an increased mammary tumor risk. This difference between omega-3 and omega-6 levels was found to be caused mainly by Eicosatrienoic acid. It is concluded that omega fatty acids mayplay an important role in the biological mechanism of mammary tumour in female dogs.